High resolution beam switch antenna based on modified CRLH Butler matrix. Issue 1 (14th October 2020) - Karimian, Reza; Dashti Ardakani, Mansoor; Ahmadi, Shahrokh; Zaghloul, Mona
Abstract: A new beam switch antenna based on a composite right/left‐handed (CRLH) Butler matrix is presented and experimentally validated. The CRLH transmission line (TL) is proposed to increase the number of beams. The proposed CRLH TL has more than 100° phase difference using variable bias voltages. Different combinations of phase shifts are achieved by applying different bias voltages between 0 and 8 V. The CRLH TL is added to the conventional Butler matrix to increase the progressive phase difference between adjacent ports, and consequently, the beam pattern. A 5° beam resolution within a spatial range of 100° is achieved. The measurement results are in good agreement with the simulations. Abstract : A new beam switch antenna based on a CRLH Butler matrix is presented and validated. The CRLH transmission line is added to the conventional butler matrix to increase the progressive phase difference between adjacent ports, and consequently, the beam pattern. A 5° beam resolution within a spatial range of 100° is achieved by using a modified Butler matrix utilizing a CRLH phase shifter. The measurement results are in good agreement with the simulations.